Evaluation of national reassurance policing programme, 2003-2006 (Opinions and Lifestyle Survey, 2014)
This data collection consists of the telephone survey responses from all three waves of the National Reassurance Policing Programme (NRPP) evaluation. The NRPP preceded the national roll-out of neighbourhood policing and sought to improve public confidence in policing. It involved local communities in identifying priority crime and disorder issues in their neighbourhood which they then tackled together with the police and other public services and partners. The NRPP ran trials of reassurance policing in 16 ward level sites, in eight forces in England, beginning in October 2003. The programme was evaluated at the end of the first year of implementation. Overall, the programme was found to have a positive impact on crime and anti-social behaviour, public feelings of safety, and public confidence in the police. In the second year of the programme, four of the original NRPP sites were selected for continued evaluation to test whether the results achieved in the first year could be sustained in the longer term. The main evaluation of the NRPP's first year covered six sites each matched with a control. Outcomes were measured using police statistics and a telephone survey in each site, where the same respondents were interviewed at the outset of the programme and one year later. A sample of 300 respondents was selected randomly with a panel sample of 200 achieved in each site. The baseline survey was conducted between November 2003 and January 2004, and the follow-up survey between November 2004 and January 2005. The sustainability of programme effects in year two was assessed by a third wave of the survey carried out between November 2005 and January 2006. In each site, a panel sample of about 160 was achieved. It consisted of 'original respondents' interviewed in waves 1, 2 and 3 of the survey, and 'new respondents' interviewed in only waves 2 and 3.